The Acting Chair's Summing Up : Independent Evaluation Office-Self Evaluation at the IMF-An IEO Assessment. (Policy Papers; Policy Paper ;, 2015)
Executive Directors welcomed the report by the Independent Evaluation Office (IEO) on self-evaluation at the IMF, the accompanying statement on the report by the Managing Director, and the IEO's response. They were encouraged by the report's findings that there is considerable self-evaluation at the IMF; that such self-evaluation is generally of high quality; and that it contributes usefully to reforms in policies and operations. At the same time, they also noted the finding that there are gaps and weaknesses in the Fund's self-evaluation. Against this background, Directors considered the recommendations of the report to adopt an overall policy for self-evaluation; conduct self-assessments for every IMF-supported program; explicitly set out a plan for how policies and operations will be self-evaluated; and better disseminate lessons from self-evaluation. In this context, many Directors supported strengthening the current mechanisms for self-evaluation. More broadly, Directors agreed on the importance of having a clearly articulated approach to self-evaluation that builds on current processes, takes due account of resource constraints, and adapts over time to changing circumstances. Directors also concurred on the need to better disseminate lessons from self-evaluation. The implementation plan would be a first opportunity to reflect on how best to carry these considerations forward.